Mineralization, anti-demineralization, and antibacterial effects of novel Bioactive Universal Bond with calcium salt monomers on dental caries - Altankhishig, Bayarchimeg; Matsuda, Yasuhiro; Rao, Yaxin; Saito, Takashi (Frontiers in Dental Medicine, 2025)
This study investigated the mineralization, anti-demineralization, and antibacterial properties of a novel bioactive universal adhesive containing the calcium salt of 4-methacryloxyethyl trimellitate acid (CMET). Four adhesives were evaluated: Bioactive Universal Bond with CMET (BA), Clearfil Universal Bond Quick (CU), Prime & Bond Universal (PB), and Scotchbond Universal Plus Adhesive (SUB). To assess mineralization properties, BA specimens were immersed in simulated body fluid (SBF) at 37°C, in line with ISO 23317, and the induced crystals were analyzed using scanning electron microscopy and energy dispersive x-ray spectroscopy. Anti-demineralization was evaluated by applying each adhesive to polished bovine dentin, followed by a one-week pH cycling protocol. Transverse microradiography (TMR) was used to quantify the integrated mineral loss. The antibacterial activity was assessed using eluates prepared by immersing the cured specimens in distilled water for seven days, followed by serial dilutions (10%, 5%, 1%, and 0.5%). These eluates were incubated with Streptococcus mutans, Actinomyces viscosus, and Lactobacillus casei for 24 h at 37°C. Viable bacterial counts were determined using the quantitative polymerase chain reaction following propidium monoazide treatment. BA exhibited distinct mineralization in SBF, likely attributable to CMET, and was characterized by the formation of octacalcium-phosphate-like crystals. TMR analysis showed that BA significantly suppressed demineralization at the dentin–material interface in relation to the other adhesives. In antibacterial assays, 5% and 10% BA eluates markedly suppressed the growth of S. mutans and A. viscosus, whereas CU, PB, and SUB exhibited inhibitory effects at only 10% concentration for S. mutans and had no impact on A. viscosus. Notably, only the 10% BA eluate significantly inhibited L. casei growth. Despite the limitations of the in vitro experiments, these findings suggest that BA possesses multifunctional properties, supporting its potential as an effective adhesive system for the prevention and treatment of caries. Furthermore, its demonstrated bioactivity suggests promising applications across various biomedical fields, such as antibacterial coatings for medical devices, bone-regenerative scaffolds, and bioactive interfaces in tissue engineering and regenerative medicine.